2015
DOI: 10.1111/cgf.12634
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Impact of Visual Embellishments in Bar Charts

Abstract: A B C 0 100 (a) Bars extend below zero line. A B C 0 100 (b) Triangle bar chart.Figure 1: Two examples of embellished charts and abstracted versions of the embellishments. AbstractAs data visualization becomes further intertwined with the field of graphic design and information graphics, small graphical alterations are made to many common chart formats. Despite the growing prevalence of these embellishments, their effects on communication of the charts' data is unknown. From an overview of the design space, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 17 publications
(21 reference statements)
0
34
0
1
Order By: Relevance
“…They actually may be good to attract attention and entertain, but their utility, from the point of view of quantitative rigor, is questionable. A recent study showed that, for bar charts, most embellishments reduce the accuracy estimating quantities [1], while Zacks et al [2] had previously shown that some extraneous features, such as 3D volumetric bars, also harm perception.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…They actually may be good to attract attention and entertain, but their utility, from the point of view of quantitative rigor, is questionable. A recent study showed that, for bar charts, most embellishments reduce the accuracy estimating quantities [1], while Zacks et al [2] had previously shown that some extraneous features, such as 3D volumetric bars, also harm perception.…”
Section: Previous Workmentioning
confidence: 99%
“…This amounts a total of 72 charts, with 2 bars per chart, which makes 144 answers per user. The values of the bars were generated randomly in the range [3,97], to prevent overly simple judgments where the bars might be completely aligned with the axis, as suggested in [1]. This experiment was performed in a controlled environment with displays of 21-24 inches in good lighting conditions.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in this direction explores how additional visual cues and reference structures can improve perception. Skau et al [SHK15] studied visual embellishments in bar charts and found that they indeed have an impact on the effectiveness of perceiving the chart data. Reference structures such as grids and tick marks are frequently recommended for data charts to aid in relating content to axes [Kos06].…”
Section: Related Workmentioning
confidence: 99%
“…Visual embellishments, e.g., rounded tops for bar charts, can impact absolute and relative judgments negatively [Skau et al, 2015]. While one study found a relation between a high data-ink ratio and faster response times as well as greater accuracy under specific conditions [Gillan and Richman, 1994], others could not confirm these results [Spence, 1990;Blasio and Bisantz, 2002;Kulla-Mader, 2007;Moere et al, 2012].…”
Section: Perception and Data Representationmentioning
confidence: 99%